2022
DOI: 10.1158/1538-7445.panca22-c020
|View full text |Cite
|
Sign up to set email alerts
|

Abstract C020: Neutrophil-mediated stromal-tumor IL-6/STAT-3 signaling underlies the association between neutrophil-to-lymphocyte ratio dynamics and chemotherapy response in localized pancreatic cancer: A hybrid clinical-preclinical study

Abstract: Background: Partial/complete pathologic response following neoadjuvant chemotherapy (NAC) in pancreatic cancer (PDAC) patients undergoing pancreatectomy is associated with improved survival. We sought to determine whether neutrophil-to-lymphocyte ratio (NLR) dynamics predict pathologic response following chemotherapy in PDAC, and if manipulating NLR impacts chemosensitivity in preclinical models and uncovers potential mechanistic underpinnings underlying these effects. Methods: Pathologic response in PDAC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The dynamics of NLR and its potential to predict chemotherapy response have also been studied in preclinical models. These studies have shown that treatments that reduce NLR not only significantly downstage tumor burden and metastatic growth, but also increase the presence of tumor-infiltrating CD8+ T cells, thereby dampening fibroblast polarization and chemo-resistance signaling pathways [16].…”
Section: Predictive and Prognostic Role Of Neutrophil To Lymphocyte R...mentioning
confidence: 99%
“…The dynamics of NLR and its potential to predict chemotherapy response have also been studied in preclinical models. These studies have shown that treatments that reduce NLR not only significantly downstage tumor burden and metastatic growth, but also increase the presence of tumor-infiltrating CD8+ T cells, thereby dampening fibroblast polarization and chemo-resistance signaling pathways [16].…”
Section: Predictive and Prognostic Role Of Neutrophil To Lymphocyte R...mentioning
confidence: 99%